Programa de actividad física deportiva como medio terapéutico para niños con trastornos con déficit de atención e hiperactividad TDAH) en el marco escolar (2023)
This reportfocusesonthedevelopmentofintershipsentitledwiththename sportsphysicalactivityprogram atherapeuticmeansforchildrenwithattention déficithyperactivity disordersintheschoolsetting.Attentiondéficithyperactivity disorder(TDAH)isagroupofcharacteristics,mainlyinattention,hyperactivityand impulsivity,thatslowdowntheperformanceofpeoplewhohaveit,thusgeneratingan impactontheirdailylives.ThroughtheapplicationofatestcalledEFECOwhichallows ustoassessexecutivefunctionsbasedonthebehavioralreportreportofthesubject’s dailylife,madeatthebeginningandendoftheprogram,whicchseekstoimprove qualityoflifeofthepopulationinschoolchildrenagedbetween7and12yearsofthe cityofMonterìa.attentiondéficithyperactivitydisorder,throughtherapeuticlinesthathelpimprovethe